Efficacy of Radiation Therapy for the Treatment of Sialocele in Dogs. (13th November 2017) - Poirier, V.J.; Mayer‐Stankeová, S.; Buchholz, J.; Vail, D.M.; Kaser Hotz, B.
Abstract : Background: Sialocele is a collection of saliva that has leaked from a damaged salivary gland or duct and is surrounded by granulation tissue. Surgery is the recognized first‐line treatment. Recurrence rate after surgery is 5–14%. Salivary gland tissue is very sensitive to radiation therapy (RT). Hypothesis/Objectives: Radiation therapy will be useful for the treatment of sialocele. The aims were to characterize response rate and clinical course of dogs with sialocele treated with RT and to determine a starting dose for clinical use. Animals: Eleven dogs with sialocele. Methods: Retrospective study of response and outcome after RT. Results: All dogs had cervical sialocele. Seven dogs (63.6%) were treated with 3 weekly fractions of 4 Gray (Gy); (total dose, 12 Gy). Three dogs (27.3%) received 4 fractions of 4 Gy (16 Gy) and 1 dog received 5 fractions of 4 Gy (20 Gy) on a Monday‐Wednesday‐Friday schedule. Six dogs (54%) achieved a complete response (CR), and 5 dogs (45%) achieved a partial response (PR). Three dogs had progression of their sialocele 2, 3, and 9 months after RT; all three had received 12 Gy initially and 2 received 2 additional fractions of 4 Gy (cumulative total dose, 20 Gy) and subsequently achieved remission for >2 years. Conclusions and Clinical Importance: Radiation therapy is useful for the treatment of recurrent sialocele refractory to surgical management and a minimum total dose of 16 or 20 Gy in 4 Gy fractions appears effective.